Optical up-conversion for WDM-RoF transmission using multiple optical carrier suppression in OFCG. (March 2016) - Zhang, Chan; Ning, TiGang; Li, Jing; Chen, Hongyao; Li, Chao; Liu, Zhiming
Abstract: A tunable optical frequency comb generator (OFCG) by cascading an Electro-absorption modulator (EAM) followed by a phase modulator (PM) and an intensity modulator (IM) is proposed for wavelength division multiplexing radio-over-fiber (WDM-RoF) transmission. The generated OFCG serves as the carriers of WDM-RoF system to realize all-optical up-conversion afterwards. In the proposal, each comb line is modulated by the radio-frequency (RF) signal via multiple optical carrier suppression (OCS) after optical comb generation. We have systematically compared the performances of the optical up-conversion based on different modulation schemes. Among three schemes, the OCS modulation scheme shows the highest receiver sensitivity and smallest power penalty over long-distance transmission. What's more, the OCS modulation scheme can be easily implemented with a large number of WDM channels simultaneously without any power saturation or other nonlinear impact. In the numerical simulation, 15 WDM channels each carrying 15 Gb/s×5 Gb/s baseband signal have been up-converted to 10 GHz simultaneously. This method still provides high performance after 20 km transmission, which shows simple cost-efficient configuration and good performance over long distance delivery. Highlights: A novel optical up-conversion for WDM-RoF transmission is proposed. The number and spacing of OFCG can be easily tuned. Different performances based on different modulation scheme is studied. 15 WDM channelshave been up-converted simultaneously with good BER. The scheme is a simple cost-efficient for optical-wireless access communication.